Mechanization of sugarcane cultivation in Fiji – status and way forward - Rahul Ravneel Prasad; Vinal Vishal Chand; Shivneel Krishneel Narayan; Ashneil Nadan (Journal of Sugarcane Research, 2023)
Sugarcane is Fiji’s most important commercial crop, with the sugar industry being the largest enterprise in the country. The industry employs close to 48,000 individuals, with a quarter of the country’s population depending directly and indirectly on the industry for their livelihoods, despite the subsiding sugar industry and declining yields observed in the past two decades. Therefore, to increase yield per hectare and solve the labour storage problem, there has been an immense focus on the mechanization of the sugar industry. There is very little documentation regarding the mechanization of sugarcane farming in Fiji, hence, the present study was undertaken to determine the status of farm mechanization in sugarcane production, using the Nadogo district of Vanua Levu, Fiji, as a case study site. The study revealed that to increase the productivity of the farm and reduce the cost of cultivation, farmers in the Nadogo district were attempting to adopt various mechanisation strategies related to land preparation, planting of sugarcane crops, intercultural operations, weedicide application, harvesting, ratoon management, and transportation of the harvests. In the study, we also focus on the advantages and disadvantages related to the mechanization of the sugarcane farms. The study revealed advantages such as saving time and labour for the growers, minimizing drudgery, improving work quality, lowering operating costs, and ensuring optimal resource utilization related to farm mechanization. The disadvantages were high maintenance costs due to wear and tear, the high cost of fuel to use some of the machinery, increased carbon footprints, and pollution. Most of these machines were also causing soil compaction during rainy seasons and delaying the cultivation process when machine breakdowns occurred and parts were not available.